Principal's Trilogy Leadership Style And Teacher Productivity In Islamic Elementary School Of East Java Province, Indonesia - Azis, Abdul (2014)
This study is intended to investigate the influence of principal's trilogy leadership style on teacher productivity in Islamic elementary school of East Java Province, Indonesia. This study defines some research problems as follows: the level of principal's trilogy leadership practice, the characteristics of principal's trilogy leadership style, the difference of principal's trilogy leadership style according to location and category of Islamic elementary school, the difference of teacher productivity according to location and category of Islamic elementary school, the influence of principal's trilogy leadership style on teacher productivity in Islamic elementary school, and how successful principal generates teacher productivity in Islamic elementary school. In this case, the study